Effectiveness of Mobile Applications in Mental Health Counseling for Pregnant Women : A Systematic Review - Ririn, Ririn; Putri, Aulia; Sigalingging, Muslimah; Rohani, Rohani; Astuti, Andari Wuri; Mahardya, Rizky Tsalatshita Khair (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Mental health technology, especially versatile mobile applications, can aid in treating prenatal depression, which affects 12% of pregnant women.Objective: This systematic review aims to gather the latest evidence on the effectiveness of mobile applications for mental health support among expectant mothers.Methods: The methodology followed the PRISMA guidelines for systematic reviews and meta-analyses, utilizing a systematic review design. The PICOS framework guided the search strategy. A literature search was performed using PubMed, Wiley, and ScienceDirect. The inclusion criteria encompassed seven original, English-language studies published between 2019 and 2024, focusing on the effectiveness of mobile applications in mental health counseling for pregnant women. All studies employed a randomized controlled trial design. The Cochrane Risk of Bias 2 tool was used to assess the quality of each study. Results: The articles were sourced from Germany, Singapore, Brazil, China, Japan, the Netherlands, and South Korea. All seven studies utilized a randomized controlled trial design with quantitative research. The risk of bias assessment revealed five studies with concerns and two with low risk. Pregnant women using these apps reported lower levels of depression and anxiety, along with enhanced social support, indicating that these applications offer a cost-effective alternative for mental health treatment. Conslusion: App-based therapies, such as cognitive behavioral therapy and mindfulness training, have been shown to improve mental health and prenatal care. While the results are promising, some studies suggest further evaluation is needed to fully understand the efficacy of technology-based interventions. Overall, mobile app technology holds significant potential for improving perinatal health outcomes and supporting the mental